PERTANGGUNGJAWABAN PIDANA DALAM KEJAHATAN PERBANKAN - Yohana Yohana; Alvi Syahrin; Muhammad Hamdan; Mahmul Siregar (USU LAW JOURNAL, 2014)
ABSTRACT Human economic life at this time is closely related to banking. Banking serves as a crutch to help the needs of human life by running the bank business. Law No. 10 of 1998 defines a bank as a legal entity which collects funds from the public in the form of savings and distribute them to the public in the form of loans and / or other forms in order to improve the living standard of the people. Types of crime in the banking world is related to licensing (the crime of illegal bank), bank secrecy, the bank business, as well as the supervision and guidance of banks. The imposition of criminal responsibility is certainly a must satisfy the two other elements of an error or flaw in the nature of the act and the absence of a good reason for removal of criminal justification or an excuse. Keywords : Criminal Responsibility, Crime Banking.